Adjusting the training of experienced long jumpers - Makaruk, H. (New Studies in Athletics, 2007)
Near the end of an athlete's career, the adaptation capacities of the organism decline. Increasing the training load, or even maintaining the current level, becomes difficult and it is imperative to find new quality solutions. The aim of this study was to identify a training structure that would make it possible for long jumpers to extend their careers. Data characterising the training of elite long jumpers was analysed from two points of view: informative (the type of exercises implemented) and energetic (the type of energy sources). The results show that it is indispensable to maintain a high level of maximum intensity loads and, unexpectedly, contradicts the common belief that the training of experienced athletes should be mainly specialised. It is suggest that experienced long jumpers should make regular use of "oriented" loads, which are structurally and functionally similar to their event but not as dose to the performance movement as "special" exercises.